Effect of microstructural evolution from nano to micron grain size regime towards structural, magnetic, electrical and microwave properties of gadolinium iron garnet (Gd3Fe5O12) - Farah Nabilah Shafiee; Muhammad Syazwan Mustaffa; Nor Hapishah Abdullah; Mohd Nizar Hamidon; Ismayadi Ismail; Rodziah Nazlan; Idza Riati Ibrahim; Fadzidah Mohd Idris; Mohd Shamsul Ezzad Shafie (Springer Nature Switzerland AG, 2024)
Indexed by WOS/SCOPUS/ERA